2007
DOI: 10.2337/dc06-1400
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Menopause on the Metabolic Syndrome Among Korean Women

Abstract: OBJECTIVE -This study examined the effect of menopausal status on the risk of the metabolic syndrome in Korean women. RESULTS -Postmenopausal women had significantly higher mean waist circumference, systolic blood pressure, pulse pressure, total cholesterol, LDL cholesterol, and triglyceride levels than premenopausal women after adjusting for age (P ϭ 0.018, P ϭ 0.001, P Ͻ 0.0001, P Ͻ 0.0001, P Ͻ 0.0001, and P ϭ 0.006, respectively). Among postmenopausal women, the ageadjusted odds ratio was 1.61 (95% CI 1.15-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
94
6
13

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(134 citation statements)
references
References 34 publications
19
94
6
13
Order By: Relevance
“…No entanto, entre 20 e 50 anos de idade, os homens apresentam uma maior prevalência de síndrome metabólica; a partir dos 50 anos, a prevalência torna-se maior entre as mulheres. Sugere-se que a fase da transição menopáusica possa ser um determinante importante no aumento dessa prevalência 8 .…”
Section: A Síndrome Metabólica Na Transição Menopáusicaunclassified
See 2 more Smart Citations
“…No entanto, entre 20 e 50 anos de idade, os homens apresentam uma maior prevalência de síndrome metabólica; a partir dos 50 anos, a prevalência torna-se maior entre as mulheres. Sugere-se que a fase da transição menopáusica possa ser um determinante importante no aumento dessa prevalência 8 .…”
Section: A Síndrome Metabólica Na Transição Menopáusicaunclassified
“…Na Coreia do Sul, o aumento da prevalên-cia de obesidade abdominal na pós-menopausa foi aproximadamente de 40% em relação às mulheres na pré-menopausa 8 , semelhantemente ao estudo realizado por Cho et al 21 também na Coreia do Sul, no qual este aumento foi superior a 30%. Na avaliação da média da circunferência da cintura, o estudo de coorte com 1.276 mulheres na Holanda verificou um aumentou na transição menopáusica.…”
Section: Obesidade Abdominalunclassified
See 1 more Smart Citation
“…This may happen with high prevalence of metabolic syndrome among postmenopausal women. Study of Deibert et al [42] showed that prevalence of metabolic syndrome among post-menopausal women was 36.1% and also some other studies showed that menopausal women in Canada [43], Ecuador [33] and South Korea [44] had prevalence of metabolic syndrome 31%, 41.5% and 54.6% respectively. Marjani et al showed that the prevalence of metabolic syndrome among postmenopausal women was 31% [45].…”
Section: Different Viewsmentioning
confidence: 93%
“…Studies among Korean and Chinese populations showed that prevalence of metabolic syndrome were 13.8% [44] and 17.8% for females, respectively [50]. Studies were done by Eshtiaghi [51], Ainy [52], Deilbert [42], Figueiredo Neto [53] and Heidari et al [54] have shown that prevalence of metabolic syndrome were 18.3%, 53%, 23%, 24% and 44.9%, respectively.…”
Section: Different Viewsmentioning
confidence: 99%